2011
DOI: 10.5665/sleep.1428
|View full text |Cite
|
Sign up to set email alerts
|

Race and Residential Socioeconomics as Predictors of CPAP Adherence

Abstract: Black race and lower socioeconomic residential areas are associated with poorer adherence to CPAP in subjects with standardized access to care and treatment. Disparities remain despite provision of standardized care in a clinical trial setting. Future research is needed to identify barriers to adherence and to develop interventions tailored to improve CPAP adherence in at risk populations. Portable Monitoring for Diagnosis and Management of Sleep Apnea (HomePAP) CLINICAL TRIAL INFORMATION: NIH CLINICAL TRIALS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
143
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 163 publications
(157 citation statements)
references
References 33 publications
11
143
1
2
Order By: Relevance
“…13,20,[44][45][46][47][48] Our data, which include subjects with a wide range of SDB severity and sleepiness as well as wide ranging racial and gender distribution, are in agreement with studies that showed no relationship between these demographic variables and short-term or long-term CPAP use. In our dataset with 27% Black subjects, we failed to show a difference in ST CPAP adherence based on race (Black subjects: 3.2 ± 2.0 h/night vs White subjects: 3.2 ± 2.4 h/night, p = 0.99).…”
Section: 3839supporting
confidence: 74%
See 1 more Smart Citation
“…13,20,[44][45][46][47][48] Our data, which include subjects with a wide range of SDB severity and sleepiness as well as wide ranging racial and gender distribution, are in agreement with studies that showed no relationship between these demographic variables and short-term or long-term CPAP use. In our dataset with 27% Black subjects, we failed to show a difference in ST CPAP adherence based on race (Black subjects: 3.2 ± 2.0 h/night vs White subjects: 3.2 ± 2.4 h/night, p = 0.99).…”
Section: 3839supporting
confidence: 74%
“…In our dataset with 27% Black subjects, we failed to show a difference in ST CPAP adherence based on race (Black subjects: 3.2 ± 2.0 h/night vs White subjects: 3.2 ± 2.4 h/night, p = 0.99). Other studies have showed significantly reduced CPAP adherence in black subjects, 30,46,47 although most of these studies did not report socioeconomic status, which has been shown to be an independent predictor of CPAP adherence regardless of race.…”
Section: 3839mentioning
confidence: 87%
“…There is increasing evidence that African Americans have disproportionate failure rates following adenotonsillectomy for OSA in children and reduced rates of CPAP adherence for OSA in adults. 22,23 Other vulnerable groups have also been found to have lower CPAP adherence. 24 Little information is available regarding the success of specific OSA treatment options in South Asians.…”
Section: Sleep Apnea and Cardiometabolic Risk In South Asiansmentioning
confidence: 99%
“…The current standard of treatment for moderate to severe OSAS is positive airway pressure (PAP) therapy [2]. However, diagnosis and treatment methods are expensive, and often unaffordable to those that are economically challenged and/or uninsured [3,4,9]. Reports in the literature suggest that patients from lower SES backgrounds encounter barriers to diagnosis of OSAS and have lower therapy adherence rates [3,4,7,9].…”
Section: Introductionmentioning
confidence: 99%